Projected Dryland Cropping System Shifts in the Pacific Northwest in Response to Climate Change - Karimi, Tina; Stöckle, Claudio O.; Higgins, Stewart S.; Nelson, Roger L.; Huggins, David (Frontiers in Ecology and Evolution, 2017)
Agriculture in the dryland region of the Inland Pacific Northwest (IPNW, including northern Idaho, eastern Washington and northern Oregon) is typically characterized based on annual rainfall and associated distribution of cropping systems that have evolved in response to biophysical and socio-economic factors. Three agro-ecological classes (AEC) have been proposed for the region: a) crop/fallow (CF), b) annual crop/fallow transition (CCF), and c) continuous cropping (CC). AECs attempt to associate land use into relatively homogeneous areas that result in common production systems. Although there is an interest in sustainable intensification of cropping systems (e.g., reduction of fallow), the question remains whether climate change will preclude intensification or shift the borders of existing AECs toward greater fallow utilization. A simulation study was conducted to address this question, with the aim of classifying 4x4 km pixels throughout the region into one of the three AECs for baseline (1979-2010) and future periods (2030s, 2015-2045; 2050s, 2035-2065; 2070s, 2055-2085). Baseline data were derived from traditional rotations and historical climate records. Data for future projections were derived from atmospheric CO2 concentration considering daily weather downloaded from 12 global circulation models and 2 representative concentration pathways (RCP 4.5 and 8.5). Due to the direct effect of atmospheric CO2 on photosynthesis and stomatal conductance, the transpiration use efficiency of crops (TUE; g above-ground biomass kg water-1) showed an increasing trend, with winter wheat TUE changing from 4.76 in the historical period to 6.17 and 7.08 g kg-1 in 2070s, depending on AEC. Compared to the baseline, total grain yield by the 2070s in the region was projected to increase in the range of 18% to 48% (RCP 4.5) and 30% to 65% (RCP 8.5), depending on AEC. As a consequence of these changes, compared to the historical baseline period, the future fraction of the area classified as CF decreased from 50% to 39-36%, CC increased from 16% to 24-28%, and CCF decreased slightly (~1%), with the greater change projected for the RCP 8.5 scenario.